Correlation of Absolute Lymphocyte Count with Severity of COVID-19 at Dr. Mohammad Hoesin General Hospital Palembang - Zen Ahmad; Yulia Nugraha Karsita; Phey Liana; Erial Bahar (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: The rRT-PCR examination is very effective as a diagnostic tool for COVID-19 but cannot be a full reference as an evaluation examination because rRT-PCR is able to capture the genetic material of the virus without ensuring that the virus is still alive or only dead particles. This study aims to explore the correlation between absolute lymphocyte values and the severity of COVID-19 at Dr. Mohammad Hoesin General Hospital Palembang. Methods: This study is an observational study involving 413 research subjects at Dr. Mohammad Hoesin General Hospital. Data analysis was carried out univariate and bivariate. Results: The absolute number of lymphocytes with the severity of COVID-19 has a negative correlation, with a strong correlation strength, which is expressed by the value of r = -0.617 and the degree of significance of p = 0.000. Conclusion: There is a correlation between absolute lymphocyte count and the severity of COVID-19 at Dr. Mohammad Hoesin General Hospital Palembang.